Asset redeployability and green innovation - Do, Trung K. (Journal of Financial Stability, 2024)
We present evidence that firms with greater asset redeployability are more likely to engage in green innovation activities, as measured by corporate green patents and citations. This finding supports the notion of funding flexibility and withstands numerous robustness and endogeneity tests. The relationship is particularly pronounced for firms facing high climate change uncertainty, as well as those in high-polluting industries. Moreover, we find further evidence that the pursuit of green innovation is associated with improved firm value over the long term. These insights shed light on how asset redeployability correlates with both innovation outcomes and firm performance within the context of green finance for sustainable development.